KUALITAS PAPAN PARTIKEL DARI LIMBAH GERGAJIAN KAYU BANGKIRAI (Shorea laevis Ridl) (Quality of Particle Board From Saw Waste Wood of Bangkirai (Shorea laevis Ridl)): G.Siska, Sarinah, D.L. Bangun - JHT, Admin (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2018)
ABSTRACTThe particle board is a wood product resulting from the heat-blowing process between a woodparticle mixture or lignocellulosic raw material with an adhesive or a wood product ofreconstitution. A research on particle board manufacture was conducted using Bangkirai woodparticles bonded together with urea formaldehide (UF) adhesive. This research aimed todetermine the quality of particle board produced on its physical and mechanical properties.Particle particle size is 30 cm x 30 cm x 1 cm with target density 0,7 g / cm3. Results revealedthat UF adhesive level had an effect on moisture content, density, water absorption, thicknessswelling, MoR, MoE and screw-withdrawal strength. Density and thickness swelling that couldfavor the Japanese standards either partially or completely. Based on the value of density,particle board of this experimental results is more suitable for use as a room divider andfurniture raw materials. Particle board with 25% adhesive content provides a good prospect inthe particle board manufacturing industry.Keywords: Particleboard; physical and mechanical properties; Bangkirai wood; UreaFormaldehyde adhesive